Fire-grazer interactions in a Highveld grassland in South Africa - Skhosana, Felix Vusumuzi (My University, 2017)
Fire is known to affect spatial patterns of grazing by altering the amount and quality of forage. Animals select the post-burn green flush that remains palatable until the grass recovers its biomass. How quickly the grass regrows depends on the rainfall and grass growth rates, and also grazing intensity. Theoretically, highly concentrated grazing can maintain short (relatively more palatable) grasslands throughout a growing season. Therefore this study aimed at; i) determining how long different grazer species were attracted to the burn, and whether this increased grazing pressure (as a result of concentrating grazers on a small burnt patch) maintained a short, palatable grass sward throughout the growing season, ii) investigating the long-term impacts of herbivore attraction to small burns on grass community and landscape function in a Highveld grassland. We therefore monitored grazer utilization of an experimentally applied small (5ha) burnt patch using dung counts and camera traps, and also measured the structural changes of the burnt patch over a period of 12 months. To test whether this process of attraction to small burns could have long-term impacts on grass community composition and landscape function we quantified species composition, infiltration rates, soil compaction, soil moisture, and ANPP in another landscape which had received 10+ years of small annual burns (a firebreak). A novel finding was that indeed grazers especially the short-grass specialist stayed on the burn and kept the grass short (<10cm) for the duration of the study post fire: the burn only treatment on the 5ha burn recovered its biomass within 2 months of the first rains. This result was due to the fact that it was a drought year with half the normal rainfall (and lower grass regrowth rates). However, the long-term study indicated that the attractive effect of small fires in this ecosystem alters both community composition and ecosystem properties. The firebreak had more bare ground and less water infiltration than the surrounding grassland – but was more diverse and had higher grass productivity. It also continued to attract the short-grass specialist species (blesbok, wildebeest and hartebeest). This counter-intuitive result indicates that perhaps these grasslands are not as severely degraded as we think. This study therefore, showed that coupling small burns with appropriate grazer species has a great potential for creating palatable grazing “hotspots”, in sourveld grassland without obvious damage to ecosystem function.
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for the Master of Science degree. in School of Animal, Plant and Environmental Sciences, University of The Witwatersrand, Johannesburg July 2017.
Keywords: Grazing--South Africa; Animals--Food--Research--South Africa; Animal-plant relationships; Fires